EBV-Positive Lymphoproliferative Diseases: A New Concept and Differential Diagnosis (Literature Review and Case Reports) - АM Kovrigina (Клиническая онкогематология)
In recent years increasing attention focuses on the concept of EBV-positive lymphoproliferative diseases related to primary or secondary immunodeficiency resulting from immunosuppressive therapy and persistent infections. Due to the progress of treatment methods in oncohematology and oncology this pathology also occurs as a delayed event when new surgical and therapeutic approaches are applied. The paper presents proof for the pathogenetic significance of Epstein-Barr virus (EBV) in the pathology under consideration with its various clinical manifestations and describes the evolution of knowledge on posttransplant lymphoproliferative disorders with their morphological classification underlying EBV+ lymphoproliferative diseases. The WHO Classification of Tumours of Hematopoietic and Lymphoid Tissues revised in 2017 includes new forms of EBV+ lymphoproliferative diseases (mucocutaneous ulcer, T- and NK-cell childhood lymphoproliferative disorders including cutaneous and systemic forms of chronic active EBV infection) and EBV+ large B-cell lymphomas (unspecified and fibrin-associated diffuse large B-cell lymphomas). The paper summarizes major characteristics of these diseases and exemplifies them by the author’s own experience.